2020
DOI: 10.3791/60314
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Metastatic Clear Cell Renal Cell Carcinoma Model Established in Mouse Kidney and on Chicken Chorioallantoic Membrane

Abstract: Metastatic clear cell renal cell carcinoma (ccRCC) is the most common subtype of kidney cancer. Localized ccRCC has a favorable surgical outcome. However, one third of ccRCC patients will develop metastases to the lung, which is related to a very poor outcome for patients. Unfortunately, no therapy is available for this deadly stage, because the molecular mechanism of metastasis remains unknown. It has been known for 25 years that the loss of function of the von Hippel-Lindau (VHL) tumor suppressor gene is pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Our experience has shown that the CAM model is an efficient, time-saving in vivo model, especially for establishing human RCC xenografts [ 35 , 36 ]. Furthermore, it faithfully recapitulates the metastatic behaviors of the mouse model [ 37 , 38 ]. Here, we utilized fertilized duck eggs rather than the traditional chicken eggs because they offered a more extended tumor growth/incubation period (up to a maximum of 18 days vs. 12 days) to assess metastatic potential [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experience has shown that the CAM model is an efficient, time-saving in vivo model, especially for establishing human RCC xenografts [ 35 , 36 ]. Furthermore, it faithfully recapitulates the metastatic behaviors of the mouse model [ 37 , 38 ]. Here, we utilized fertilized duck eggs rather than the traditional chicken eggs because they offered a more extended tumor growth/incubation period (up to a maximum of 18 days vs. 12 days) to assess metastatic potential [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…To assess RCC xenografts metastasis in vivo, we established the CAM model with fertilized duck eggs as our previously published protocols [ 35 , 36 , 37 , 38 ]. Freshly laid fertilized duck eggs were incubated in a MultiQuip incubator (MULTIQUIP, E2, AISTRAL, Australia) at 37 °C with 60% humidity.…”
Section: Methodsmentioning
confidence: 99%
“…The massive redundancy of transporters responsible for glutamine uptake underscores the importance of this metabolite and the challenge of blocking its uptake in tumors. All these data suggest that [ 18 F]FGln uptake is a read-out of the Most RCC lung metastasis models are generated from direct injection of RENCA or other RCC cells [32,33] into the kidney of mice. We report one of the first direct orthotopic mouse models of ccRCC lung lesions.…”
Section: Discussionmentioning
confidence: 98%
“…This differs from clinical RCC in humans, where lung metastasis is the most common metastatic site [13,14]. This difference is because embryonic lungs have not inflated and are less vascularized than the liver prior to hatching; consequently, it is less likely to be a metastatic site [38].…”
Section: Vhl(−) Exosomes Promote Rcc Metastasis In Ovomentioning
confidence: 90%